Drechslera Cynodontis as a Potential Bioherbicide for Controlling Goosegrass (Eleusine Indica) - Chia, Shin Zhi (2009)
An ideal bioherbicide should be easy and cheap to produce, viable and efficacious in controlling target weed with definite time. Drechslela cynodontis has been reported as the potential bioherbicide for goosegrass; however, its control efficacy has several shortcomings. A study was conducted to determine the suitability of D.cynodontis as bioherbicide for controlling gooserass both in the glasshouse and in the field. In the pathogenicity test, mycelium and conidia base concentration have significant effect on disease development as indicated by the high AUDPC values and faster rate of disease development. Significantly higher disease developed (DS=100%) in treatment with 0.05g/ml mycelium and 2.5 x 106conidia/ml respectively on the four leaf-stage goosegrass 6 days after inoculation. Besides, it also caused 100% disease severity on Dactylotenium agegypyium. The fungus infected other closely related grassy weeds (disease index=3 and 4) and produced small necrotic lesions on crop plants such as rice and corn and are resistant (disease index=2) which recovered after several days. Even though D.cynodontis was suitable in various cropping situations, but a crucial understanding of the conditions under which high level of disease development is important. Drechslera sp. requires over of 12 hours of dew period for maximum disease development (DS=100%), dew period less than 12 hour resulted on less disease developed. Therefore oil emulsion (10 % palm oil) has been used to circumvent the dew period requirement, as this emulsion has helped in creating higher disease severity. Temperature between 25-300C are suitable for spore germination and appressorium formation on leave surface. When the incubation temperature was increased to 350C, conidial germination and appressorium formation were reduced. At this temperature, most infection process was stopped at the stage of germ tubes elongation. Spore germination and formation of appressorium were significantly higher in the dark (91%) compared to light (75%) at 300C. Understanding the course of the infection and development of D.cynodontis could aid in elucidating the mechanism of host death and in determine the suitability of D.cynodontis as the biocontrol agent for goosegrass. Conidia started to germinate 3 hr (40.75%) after inoculation on goosegrass in dark condition. Germ tubes were produced abundantly 6 hr (53.75%) after inoculation and penetration occurred after appressorium formation and started to colonize the epidemal cells. For the chemical herbicide interaction study, spore germination was high in treatment containing 0.25X Glyphosate (95%) compare to other herbicides at similar concentration. At this concentration, conidial germination was reduced by 80% with Metolachlor, 72% with Clethodim, 60% with Glufosinate ammonium, and 20% with Paraquat. The interaction between these chemicals and conidia germination indicated a negative linear relationship, where spore germinations are constantly decreased with the increase in herbicide concentration. Sublethal rate of herbicide combined with pathogen may incite synergistic effect, potentially increasing weed control and reducing management costs.